English for Specific Purposes for sport as a profession in Croatia: Students’ and teachers’ voices - Ana Penjak (Studies in English Language and Education)
University teaching staff in Croatia are expected to implement English Medium of Instruction (EMI) as an integral part of their teaching inventory, while students are encouraged to enrol in academic subjects taught in English. This study aimed: 1) to examine and analyse students’ and teachers’ attitudes towards the importance of using EMI, i.e., the importance of using English for Specific Purposes (ESP) for sport as a profession as an integral part of subjects delivered in English; 2) to provide feedback to all the ESP teachers regarding the necessity of creating adequate teaching materials for teaching ESP for sport as a profession. The study sample consisted of 91 students and 32 teachers randomly selected from one of the public universities in Croatia. Data was collected using an adapted questionnaire. The reliability of the questionnaire was confirmed since the t-test for dependent samples showed no significant differences between the first and second measurements (p 0.05), and the correlation was moderate to high (r ranged between 0.71 and 0.89; p 0.05). The results show that the usage of ESP enhances the teaching and learning process and enriches their general knowledge of English. Also, the findings point towards the necessity of accumulating the number of teaching hours for subjects that implement EPS for sport as a profession and their availability at the academic level.